PENGARUH KUALITAS PELAYANAN MUTU AKADEMIK TERHADAP KEPUASAN MAHASISWA PROGRAM STUDI S2 MAGISTER MANAJEMEN FAKULTAS EKONOMI UNIVERSITAS BATANGHARI JAMBI - M. Alhudhori (Jurnal Ilmiah Universitas Batanghari Jambi, 2015)
The formation of the education system as pranata strong social and authoritative to empower all citizens indonesia in order develops into quality human so that it can and proactive to meet the challenges the days of a changingBased on the act no. 12 / 2010, the level of education is higher education after secondary education, programs that include a diploma the scholars, a magister, the doctor the profession; and and the specialists, held by the university of indonesia by the culture.Work continues to make a college education, the university will establish a good image and attractive to the public if a teacher of the two aspects of quality and academic the quality of technology and service.The competence of teachers, keilmuannya be embodied in use the method of teaching, control of your emotions and discipline at a given time and providing a service for students.A conceptual quality of academic education is the mouth of a man a tool, facilities, and the curriculum. And that is reflected in the quality of teachers, The quality of learning and teaching materials and eventually be included in the form of a bunch of teaching and learning process.Quality lecturers (X1) of dimensions of quality service lecturer given in accordance with scientific kopetensi, mastery method of teaching that emotion control and discipline of the lecturer then give influence against a student on the satisfaction Study Program Management S2 Magister Faculty Economic Univercity of Batanghari. Where the size of the lecturers influence quality of 0,473 meaning what if the lecturer increased by 100 percent satisfaction then students will Study Program Management S2 Magister Fakultas Ekonomi Universitas Batanghari will increase by 47,3 %.If quality subjects (X2) of the dimensions of the quality of service given in accordance with the level of their teaching abilities lecturers , insight lecturer and creativity enough lecturers who satisfactory , then give satisfaction the effect on a student on the course of Study Program Management S2 Magister Faculty Economic Univercity of Batanghari. Where how major lessons of quality 0,384 meaning what if the lecturer increased by 100 % it will be satisfaction students a course of study magister management masters degree fakultas ekonomi universitas batanghari will be increased by 38,4 % .Product quality learning ( X3 ) of the dimensions of the quality of service given in accordance with qualitative and quantitative , then that may leave the effect on a student on the satisfaction on a course of study magister management masters degree fakultas ekonomi universitas batanghari where how major lecturer of quality 0,408 meaning what if the learning outcomes increased by 100 % it will be satisfaction students a course of Study Program Management S2 Magister Faculty Economic Univercity of Batanghari. will increase about 40.8 % .key words : service quality, satisfaction, competition.